If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 32(20x + -60) = 16(40 + -1x) Reorder the terms: 32(-60 + 20x) = 16(40 + -1x) (-60 * 32 + 20x * 32) = 16(40 + -1x) (-1920 + 640x) = 16(40 + -1x) -1920 + 640x = (40 * 16 + -1x * 16) -1920 + 640x = (640 + -16x) Solving -1920 + 640x = 640 + -16x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '16x' to each side of the equation. -1920 + 640x + 16x = 640 + -16x + 16x Combine like terms: 640x + 16x = 656x -1920 + 656x = 640 + -16x + 16x Combine like terms: -16x + 16x = 0 -1920 + 656x = 640 + 0 -1920 + 656x = 640 Add '1920' to each side of the equation. -1920 + 1920 + 656x = 640 + 1920 Combine like terms: -1920 + 1920 = 0 0 + 656x = 640 + 1920 656x = 640 + 1920 Combine like terms: 640 + 1920 = 2560 656x = 2560 Divide each side by '656'. x = 3.902439024 Simplifying x = 3.902439024
| 3(x-5)=2x+9 | | 0.5x=-x+11 | | 2x+4=4x+10 | | 8+z=14 | | 5x-18*x=-36 | | 8x+x=63 | | 2x+4=4x+19 | | -0.125=2(x-1) | | 56t^2-19t=15 | | 32-0.2c=1 | | -13=16+m | | 174x=180(x-700) | | -12n+16=-8n-16 | | 2-p=p+2 | | 5x(x-6)=9+(x-2)(5x-2) | | 67=17+5x | | 6(x+3)=12x-12 | | 10x*20x-41*2=4 | | 3x-5(x+2)=8x+10 | | (5x+4)-2(x+1)= | | 8(60-80x)=112 | | 6y+39=-9(y-1) | | 8(60-80x)=11.2 | | z+(-7)=-8 | | 6x-2=7x-24 | | -4=4(6y-12)-2 | | .75y-1=2 | | -7(x+5)+1=9(x-9)+23 | | 35x-65=45x+125 | | 28-2.2j=11.6j+262.6 | | 5x=-3x+64 | | 48+6a=15+15a |